PRAGMA-GRAMATIKAL KESANTUNAN HEGEMONIS BAHASA BALI DALAM AWIG-AWIG - Nengah Arnawa; I Wayan Gunartha; I Nyoman Sadwika (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2018)
This study aims to reveal the relation between pragmatics and grammar, especially in Balinese language, which usually has been widely separated. The data were collected through document recording on a number of manuscripts and interviews with informants spreading out over five districts/cities in Bali Province as a representation of dialectal variation. Based on the theory of semantic structure it revealed that grammatical choice was motivated by pragmatic needs to realize Balinese hegemonic politeness in awig-awig of pakraman of the villages. The grammatical choices were: (1) personification of nouns desa, banjar, or subak, i.e. [+ CONCRETE] given the role as noun [+ HUMAN]. This grammatical choice is motivated by the adherence of members to the adat (custom) institutions. (2) Agents' dissipation to accentuate actions, especially those with negative images. This choice of syntactic structure is motivated by the maxim of wisdom and face-saving to reduce threats to someone.